Perceptions of musical ability among a sample of adults in Turkey - Dursun, Yusuf; Sager, Turan (SAGE PUBLICATIONS INC, 2026)
This study explored how adults in Turkey conceptualize musical ability through a mixed-methods design. Open-ended responses from 1,153 participants were thematically analyzed and categorized into six overarching themes. The most prevalent conceptualization defined musical ability as an innate, divinely inspired gift from God and an expression of the soul (32.7%), followed by themes of effort and learning (27.7%), emotional expressiveness (14.9%), privilege and specialness (9.4%), harmony with nature (8.2%), and creative freedom (7.1%). Quantitative analyses revealed significant demographic variations: women more frequently emphasized innate and spiritual qualities, while men highlighted creativity and autonomy; amateur musicians associated ability with emotion, whereas professionals placed less emphasis on this theme. Instrument players stressed discipline and learning, whereas non-players prioritized expressiveness. Regional patterns also emerged (e.g., Mediterranean participants favored spiritual definitions; Southeastern Anatolians highlighted nature-based intuitions). In contrast, perceptions were relatively stable across age, education, occupation, and socioeconomic status (SES), though subgroup trends (e.g., lawyers emphasizing effort) suggested nuanced social influences. These findings support socio-constructivist views of musical ability as both culturally situated and experientially shaped. The study contributes to cross-cultural music psychology by emphasizing the need for culturally responsive pedagogies that acknowledge diverse beliefs, experiences, and developmental trajectories in musical potential.
Keywords: musical ability; social perceptions; demographic variation; content analysis; mixed methods; PLASTICITY; UNIVERSALS; Psychology; Music